2005
DOI: 10.2337/diabetes.54.3.751
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of Glucose From Skeletal Muscle to Adipose Tissue During Catch-Up Fat

Abstract: Catch-up growth, a risk factor for later obesity, type 2 diabetes, and cardiovascular diseases, is characterized by hyperinsulinemia and an accelerated rate for recovering fat mass, i.e., catch-up fat. To identify potential mechanisms in the link between hyperinsulinemia and catch-up fat during catch-up growth, we studied the in vivo action of insulin on glucose utilization in skeletal muscle and adipose tissue in a previously described rat model of weight recovery exhibiting catch-up fat caused by suppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
113
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 145 publications
(129 citation statements)
references
References 36 publications
14
113
0
2
Order By: Relevance
“…In addition, the findings from indirect calorimetry of NPRQ values greater than 1 suggest that the increased lipid deposition typical of refed rats is partly the result of the occurrence of a higher rate of de novo lipogenesis in refed rats than in controls. This result is well in agreement with the "glucose redistribution hypothesis" [7,21], according to which the insulin-resistant state of skeletal muscle found in refed rats is of central importance in sparing glucose that can be diverted toward de novo lipogenesis and fat storage in adipose tissue. Indeed, a higher FAS activity-and hence de novo lipogenic capacity-has been reported in white adipose tissues of refed rats relative to controls [7,21].…”
Section: Further Characterization Of Thrifty Metabolism Driving Catchsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, the findings from indirect calorimetry of NPRQ values greater than 1 suggest that the increased lipid deposition typical of refed rats is partly the result of the occurrence of a higher rate of de novo lipogenesis in refed rats than in controls. This result is well in agreement with the "glucose redistribution hypothesis" [7,21], according to which the insulin-resistant state of skeletal muscle found in refed rats is of central importance in sparing glucose that can be diverted toward de novo lipogenesis and fat storage in adipose tissue. Indeed, a higher FAS activity-and hence de novo lipogenic capacity-has been reported in white adipose tissues of refed rats relative to controls [7,21].…”
Section: Further Characterization Of Thrifty Metabolism Driving Catchsupporting
confidence: 79%
“…Rats showing catch-up fat exhibit diminished subsarcolemmal mitochondrial mass and oxidative capacity in skeletal muscle [6]. In addition, in vivo insulin-stimulated glucose utilization has been shown to be lower in skeletal muscle but higher in adipose tissue of refed animals showing catch-up fat, thereby suggesting a redistribution of glucose utilization away from skeletal muscle toward de novo lipogenesis and fat storage in adipose tissue [7].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that after 1 week of refeeding, the HOMA index, but not body fat or plasma NEFA, was higher in the refed animals than in controls suggests that the state of insulin resistance during refeeding precedes the development of excess adiposity or elevations in circulating NEFA. Using this same rat model, we previously reported that after 1 week of refeeding, i.e., at a time point when their body fat, plasma NEFA, and intramyocellular lipids had not exceeded those of controls, the refed rats showed higher plasma insulin after a glucose load (12) and a lower in vivo insulin-stimulated glucose utilization in skeletal muscle, as assessed by hyperinsulinemic-euglycemic clamp techniques (13). Taken together, these previous and present studies suggest that during weight recovery, the state of suppressed thermogenesis per se may have a direct impact on the development of skeletal muscle insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…To what extent an increased ROS levels in skeletal muscle might be causative or consequential to the state of insulin resistance during refeeding is not known. However, the integration of data from our present and previous studies (12,13) underscores a potential link between diminished SS mitochondrial energetics, altered mitochondrial ROS levels, and insulin resistance in rats showing catch-up fat as a result of suppressed thermogenesis.…”
Section: Skeletal Muscle Mitochondria and Catch-up Fatmentioning
confidence: 99%
See 1 more Smart Citation